Segmentation of arctic coastal shoreline and bluff edges using optical satellite imagery and deep learning - Bagavathyraj, Harshavardhini; Vargas Zesati, Sergio; Fuentes, Olac; Peterson, Sasha; Tweedie, Craig E. (Frontiers in Environmental Science, 2026)
The Arctic coastline spans multiple countries, supports Indigenous livelihoods, and plays a vital role in the Arctic system. Rapid climate change is accelerating permafrost thaw, sea-level rise, and coastal erosion, underscoring the need for decision making to be informed by accurate delineation of tundra shoreline (instantaneous water line) and bluff edge (vegetation–slope boundary) position and change trends. To address this need, we compared two image segmentation approaches for mapping Arctic land and water interfaces from high-resolution satellite imagery. (1) U-Net, a supervised convolutional neural network trained on expert-annotated scenes, and (2) Differentiable Feature Clustering (DifFeat), an unsupervised model applied in a minimally supervised manner via expert-guided cluster selection. The shoreline and bluff edge boundaries were derived from the segmented land and water masks using an automated interface extraction approach. DifFeat achieved higher segmentation accuracy, with IoU values of 0.95 (water) and 0.92 (land), compared to U-Net’s 0.58 and 0.50, respectively. U-Net produced reliable results and benefited from infrared and vegetation spectral indices, but required extensive annotation and showed limited generalization to UAV imagery. DifFeat achieved superior results without manual annotation, reducing the dependence on labeled data and completing training 99.87% faster than U-Net. These findings highlight the complementary strengths of supervised and semi-supervised models for Arctic coastal mapping, with DifFeat offering a scalable, label-efficient solution for long-term coastal-change monitoring. Future work will integrate elevation data to further improve bluff edge feature detection.